FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PROFITABILITAS PERBANKAN SYARIAH DI INDONESIA (Studi Kasus pada Bank Umum Syariah di Indonesia Tahun 2009 –2012) - Rima Yunita (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2014)
Research on financial ratios and its effect to the profitability of banks in Indonesia have been carried out by several researchers, but research results are inconsistent. Profitability has essential means for long-term survival of banking business, because the profitability of the business showed good prospects in the future. This study intends to examine the effect of CAR, FDR, NPF, ROA, and ROA REO against Islamic bank in Indonesia. This explanatory research was conducted at the Islamic Commercial Bank at Bank Indonesia. Data collection was carried out inthe documentation, in the form of financial ratios data from the financial statements of Islamic Banks gained per month of Islamic Commercial Bank Statistical Report published by Bank Indonesia in 2009-2012. The samples are 48 financial ratios of data taken by purposive sampling. Descriptive statistics are used to see an overview of researchdata individually, and multiple linear regression was used to test the hypothesis, where the previous requirement that the classical assumptions include normality, multicollinearity, heteroscedasticity, and autocorrelation have been fulfilled. The results of multiple linear regression showed the CAR regression coefficient on ROA is 0.026 withp = 0.024; FDR regression coefficient on ROA is 0.009 with p = 0.007; NPF on ROA regression coefficient is 0.042 with p = 0.368, regression coefficient on ROA REO by -1.53 with p = 0.000, and the regression coefficient on ROA ROA of -0.029 with p = 0.000. The test results demonstrate F value 17.893 with p = 0.000, and the test results adjusted R2 0.642 shows the explanatory power of the five independent variables in this study was 64.2% on ROA; remaining 35.8% is influenced by other factors are not included in the regression model. Concluded that partially CAR and FDR, respectively have a positive and significant effect to ROA, whereas BOPO and REO have a negative and significant effect to ROA, but NPF have no significant effect on ROA.